Therapeutic Potential of Intrauterine Lactobacillus plantarum in Repeat Breeding Jaffarabadi Buffaloes with Subclinical Endometritis - Parmar, Devesh J.; Vala, Karsan B.; Bhatt, Raghuvir H.; Suthar, Vishal S.; Odedra, Mulraj D.; Nandaniya, Nirbhay R. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Subclinical endometritis (SCE) is an important uterine disorder associated with repeat breeding and reduced fertility in buffaloes. The present study evaluated the therapeutic efficacy of intrauterine Lactobacillus plantarum in SCE-affected repeat breeding Jaffarabadi buffaloes and compared its response with intrauterine antibiotic therapy. SCE was diagnosed through endometrial cytology using cytobrush technique and Whiteside test (WST). Out of 80 repeat-breeding buffaloes examined, cytobrush technique detected SCE in 50.00% (40/80) animals and served as the reference method with 100% relative efficacy, whereas WST detected SCE in 35.00% (28/80) buffaloes with 70.00% relative efficacy. The mean PMN cell score in SCE-positive buffaloes was 7.24±0.32%, compared to 1.42±0.21% in healthy buffaloes. Animals were allocated into four groups: probiotic group (intrauterine L. plantarum, n=15), antibiotic group (intrauterine levofloxacin, n=15), positive control group (normal saline, n=10) and negative control group (healthy cyclic buffaloes, n=10). Therapeutic response was assessed based on improvement in uterine cytology/WST grades, inflammatory markers, biochemical profile, and conception rates following artificial insemination (AI). Probiotic therapy improved uterine health status as indicated by reduced inflammatory cellular infiltration, improved WST grades, and favourable modulation of inflammatory markers including serum amyloid A (SAA) and IL-10, suggesting resolution of uterine inflammation and enhanced immune tolerance. The first service and overall three service conception rates were highest in the probiotic group 40.00 and 66.67% followed by antibiotic group 33.33 and 53.33%, negative control 30.00 and 50.00%, and positive control 20.00 and 30.00%, respectively. In conclusion, intrauterine L. plantarum therapy proved to be an efficient alternative to antibiotic therapy in SCE affected buffaloes hence can be recommended as a safe, economical and farmer-friendly approach for enhancing fertility, with the advantage of reducing dependence on antibiotics and supporting antimicrobial stewardship in livestock production systems.
Keywords: Buffaloes; Cytobrush; IL-10; Lactobacillus plantarum; Levofloxacin; SAA; Subclinical endometritis; Whiteside test